The Relationship between Human Capital and Economic Growth beyond Logarithmic Production Function. (8th August 2022) - Geng, Hongmei
Abstract : The problem that the relationship between human capital and industrial development goes beyond the logarithmic production function is solved, the needs of human capital's understanding of the economic development process and the lack of understanding of the relationship between human capital and development are met, and the understanding of the relationship between human investment and business development is improved. Based on the new characteristics of industry development and population emergence, this paper adopts a functional model with no further elasticity of logarithmic production, resulting in an empirical analysis of national development observations based on Chinese statistics and beyond logarithmic performance. From 2003 to 2016, 31 finance scholars were interviewed to examine the human capital process of economic development since the new century. The first is to establish a theoretical model of industry development including human capital, operations, and capital resources; the second is to establish human capital assessment tools including education, health, technology, and population migration to determine the accuracy of the measurement system. Then, the main concepts of regression analysis are used to describe the relationships or interrelationships of various factors and the development of an industry. The results show that since the beginning of the new century, my country's human capital generally includes two major themes: "education and scientific research human capital" reflects the well-being of human beings, among which "public human capital" is the main one. Won adopts a two-stage trans-logarithmic calculation and believes that South Korea's strength and capital change one by one, and the elasticity values are 0.78 and −1.42, respectively, when added to the performance. While the growth of the economy has not been separated from the increase of human and capital, the best way is human capital, which means more than population growth.